1997
DOI: 10.1152/ajpcell.1997.272.3.c794
|View full text |Cite
|
Sign up to set email alerts
|

Dual role for AlF4(-)-sensitive G proteins in the function of T84 epithelial cells: transport and barrier effects

Abstract: T84 monolayers were studied to determine the effect of AlF4, an activator of heterotrimeric G proteins, on Cl-secretion and intestinal barrier function. Basolateral (but not apical) addition of AlF4- increased short-circuit current (I(sc)) and decreased transepithelial resistance. Preincubation with the heavy metal chelator deferoxamine showed that both effects were dependent on Al3+. The effect on I(sc) was abolished by the intracellular Ca2+ chelator 1,2-bis(2-aminophenoxy) ethane-N,N,N',N'-tetraacetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These signaling molecules are attractive candidates for this process, given that TNF has been reported to activate Rho, Rac, and Cdc42 (39) and that these proteins may regulate tight junction protein distribution and epithelial barrier function (40)(41)(42)(43). To investigate the role of Rho family GTPases, we included the Rho kinase inhibitor Y27632 (44) or a Rac1 inhibitor, NSC23766 (45), in the perfusion solution of control and anti-CD3-treated animals.…”
Section: Gtp-binding Proteins Are Not Involved In the Development Of mentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling molecules are attractive candidates for this process, given that TNF has been reported to activate Rho, Rac, and Cdc42 (39) and that these proteins may regulate tight junction protein distribution and epithelial barrier function (40)(41)(42)(43). To investigate the role of Rho family GTPases, we included the Rho kinase inhibitor Y27632 (44) or a Rac1 inhibitor, NSC23766 (45), in the perfusion solution of control and anti-CD3-treated animals.…”
Section: Gtp-binding Proteins Are Not Involved In the Development Of mentioning
confidence: 99%
“…These data suggest that neither Rho kinase nor Rac1 activation are necessary for diarrhea and barrier defects that follow anti-CD3 injection. To evaluate a potential role for other GTP-binding regulators of actin structure, AlF 4 -, which triggers formation of lamellipodia and membrane ruffles and protrusions (46,47) and can affect barrier function (42), was included in the perfusion solution. This did not result in net water secretion or increased paracellular BSA flux ( Figure 5, A and B) without anti-CD3 treatment.…”
Section: Gtp-binding Proteins Are Not Involved In the Development Of mentioning
confidence: 99%
“…Additionally, a variety of intracellular signaling molecules such as c-Src, phosphatidylinositol 3-kinase, ERK, PKC, and PP2A are localized at the TJ (1,4,33). A significant body of evidence indicates that the TJ and paracellular permeability are regulated by signaling molecules, such as intracellular calcium (38), cyclic AMP (5), GTPase switch protein (9,29,34,46) and protein kinases (4,32,33,39).…”
mentioning
confidence: 99%
“…A recent study revealed that AlF 4 -enhances Cl -secretion by cultured colonic cells (T84), and this secretion is Ca 2+ dependent, and cAMP and cGMP independent (Ries et al 1997). In the present study, we confirmed that AlF 4 -elicited [Ca 2+ ] i dynamics in an intestinal crypt, and the dynamics were [Ca 2+ ] o independent.…”
Section: G-protein Activationmentioning
confidence: 99%